HLA Class I-T Cell Epitopes from trans-Sialidase Proteins Reveal Functionally Distinct Subsets of CD8+ T Cells in Chronic Chagas Disease - Alvarez, María G.; Postan, Miriam; Weatherly, D. Brent; Albareda, María C.; Sidney, John; Sette, Alessandro; Olivera, Carina; Armenti, Alejandro H.; Tarleton, Rick L.; Laucella, Susana A. (PLOS Neglected Tropical Diseases, 2008)
Author Summary At present, 16–20 million people in Central and South America are infected with Trypanosoma cruzi, the causative agent of Chagas disease in humans. The primary clinical consequence of the infection is a cardiomyopathy, which manifests in approximately 30% of infected individuals, many years after the initial infection. Our work in Chagas disease patients began as an effort to assess the range and specificity of antigens that were recognized by T cells, in particular CD8+ T cells, in individuals with long-term infections with Trypanosoma cruzi. Trans-sialidase proteins from T. cruzi are major surface and released proteins that are targets of humoral and cellular immune responses. We previously, identified a set of trans-sialidase peptides that were recognized by a very low frequency of chronically T. cruzi-infected subjects. Based on bioinformatic predictions, herein we report the identification of new trans-sialidase epitopes that are recognized by a higher proportion of T. cruzi-infected people. The functional profile of T cells specific for these peptides is characteristic of an infection with long term stimulation of the immune system, with high levels of IFN-γ-secreting T cells and low levels of IL-2 production. This set of T. cruzi peptides should prove useful for monitoring immune competence and changes in infection and disease status in individuals with chronic Chagas disease.